Financing the Millennium Development Goals : a note on two innovative mechanisms - Tourres, Marie-Aimee * (Sunway University College, 2006)
In 2000, the international community agreed on a set of poverty-reduction and human-development targets—the Millennium Development Goals (MDGs)—to be achieved by 2015. Official Development Assistance (ODA) is a source of funds for the developing world; however, the amount is not sufficient to cover the yearly $50 billion needed to meet the goals. To complement ODA, innovative financing mechanisms have been explored. Among others, the idea of a Tobin tax is again being debated. Another mechanism that has been tested since 1 July 2006 is the air-ticket tax. This paper summarises the current trends in ODA and describes how these mechanisms work.